Representasi Makanan Tradisional Jakarta Dalam Komposisi Foodporn Di Media Sosial Instagram - Rinjani, Rangga Samiaji (Sekolah Pascasarjana Institut Kesenian Jakarta, 2017)
Hashtag Foodporn is a word or a phrase used in social media world preceeded by the pound sign, which is used in a message to identify and to provide keyword for an idea inflicted by the visual of a food. Hashtag composition is one of a form of communication in Instagram. Itâ€™s development has became a phenomenon in social media and has spread all over the world, including to Jakarta. Foodporn is a jargon in the culinary world, itâ€™s presence signify that hashtag Foodporn is a visual culture already embedded in the social life of urban communities. In relation to Jakarta™s traditional dish, Foodporn binds iteself to food pictures and other hashtags as a part of communication and identification. Hashtag Foodporn for Jakartaâ€™s traditonal food which is closely related to Betawi culture, becomes an urban societyâ€™s representation of response to visual culture; an attempt to present the idea and taste contained in the taste and visuals of food. This research aimed to explain the relation between image and text in Instagram. The inseparability of Foodporn and culinary world in social media is bridged by photography, and ideas and looks perfected by Instagram.Hashtag Foodporn adalah sebuah kata atau frase dalam dunia sosial mediaâ€“ website–, yang didahului oleh tanda â€œ#â€ digunakan dalam sebuah pesan untuk mengidentifikasi dan memberikan kata kunci terhadap ide dari tampilan visual sebuah makanan. Komposisi hashtag adalah salah bentuk komunikasi dalam Instagram. Perkembangannya saat ini sudah menjadi fenomena di media sosial dan menyebar ke seluruh dunia tidak terkecuali di Jakarta. Foodporn menjadi sebuah jargon dalam dunia kuliner, kehadirannya menjadi penanda bahwaÂ hashtag Foodporn menjadi budaya visual yang tidak bisa lepas dari kehidupan sosial masyarakat urban. Dalam kaitannya dengan makanan tradisional Jakarta, Foodporn mengikatkan dirinya kepada gambarâ€“gambar makanan dengan hashtag lainnya sebagai sebuah bagian dari komunikasi dan identifikasi. Hashtag Foodporn dalam makanan tradisional Jakarta yang dekat dengan budaya Betawi, kini menjadi sebuah representasi masyarakat Jakarta yang hidup di ruang urban dalam merespon sebuah budaya visual. Penelitian ini mencoba menjelaskan hubungan antara image dan teks dalam media sosial Instagram. Foodporn dan kuliner tidak dapat dipisahkan dari dunia sosial media, fotografi menjadi alat untuk menjembataninya dan Instagram menjadi media yang menyempurnakannya dengan ide dan tampilannya.